Acid-catalysed xylose dehydration into furfural in the presence of kraft lignin. (February 2015) - Lamminpää, Kaisa; Ahola, Juha; Tanskanen, Juha
Highlights: Lignin has acid-neutralising capacity. Lignin inhibits xylose dehydration into furfural. The effects of lignin are greater in sulphuric acid than in formic acid. Abstract: In this study, the effects of kraft lignin (Indulin AT) on acid-catalysed xylose dehydration into furfural were studied in formic and sulphuric acids. The study was done using D-optimal design. Three variables in both acids were included in the design: time (20–80 min), temperature (160–180 °C) and initial lignin concentration (0–20 g/l). The dependent variables were xylose conversion, furfural yield, furfural selectivity and pH change. The results showed that the xylose conversion and furfural yield decreased in sulphuric acid, while in formic acid the changes were minor. Additionally, it was showed that lignin has an acid-neutralising capacity, and the added lignin increased the pH of reactant solutions in both acids. The pH rise was considerably lower in formic acid than in sulphuric acid. However, the higher pH did not explain all the changes in conversion and yield, and thus lignin evidently inhibits the formation of furfural.